2016
DOI: 10.1177/0003489416675357
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Idiopathic Subglottic Stenosis

Abstract: Most patients with ISS can be managed endoscopically, and IDI may be increased with steroid injection. Gastroesophageal reflux disease is a common co-morbidity. Body mass index did not change over time despite potential effects on exercise tolerance; BMI did not affect IDI. Methods to determine optimal timing for next intervention are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 17 publications
(52 reference statements)
2
46
1
2
Order By: Relevance
“…Patients and clinicians have grown accustomed to the need for yearly or even more frequent operations to prevent critical airway stenosis. Pharmacologic adjuncts to dilation procedures, such as mitomycin‐C and dexamethasone, as well as adjunctive laser use, have had some positive results, but the need for repeated operations and the associated risks have persisted. The potential to manage at least a subgroup of these patients with office‐based treatment alone is clinically important and could represent a shift in the way we approach this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and clinicians have grown accustomed to the need for yearly or even more frequent operations to prevent critical airway stenosis. Pharmacologic adjuncts to dilation procedures, such as mitomycin‐C and dexamethasone, as well as adjunctive laser use, have had some positive results, but the need for repeated operations and the associated risks have persisted. The potential to manage at least a subgroup of these patients with office‐based treatment alone is clinically important and could represent a shift in the way we approach this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a disunity in treatment over the course of the study or an intra-population variation in treatment. Heterogeneity in treatment was suspected in nine studies (60%) (1,2,5,10,12,14,16,17,19). All other studies do not specifically report a variance in endoscopic treatment (11,13,15,18,20,21).…”
Section: Patient and Treatment Characteristicsmentioning
confidence: 98%
“…Figure 4 shows a visual overview of the different techniques in the trials. It is striking to note that only 1 trial (6.7%) examined the use of an isolated technique (18) and 14 studies (93.3%) described the use of a combination of techniques (1,2,5,(10)(11)(12)(13)(14)(15)(16)(17)(19)(20)(21) respectively. Several studies reported a disunity in treatment over the course of the study or an intra-population variation in treatment.…”
Section: Patient and Treatment Characteristicsmentioning
confidence: 99%
“…Regardless of etiology, the treatment goals center around creating an open and lasting airway and are accomplished surgically. Despite the relative homogeneity of the disease presentation and population, the treatment of iSGS remains quite variable on a spectrum from endoscopic management with balloon dilation to cricotracheal resection (CTR) . Despite CTR having less recurrence than endoscopic management, there can be significant morbidity associated with undergoing the open procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relative homogeneity of the disease presentation and population, the treatment of iSGS remains quite variable on a spectrum from endoscopic management with balloon dilation to cricotracheal resection (CTR). [7][8][9][10][11] Despite CTR having less recurrence than endoscopic management, there can be significant morbidity associated with undergoing the open procedure. Questions regarding when to implement and offer CTR to the iSGS patient are important issues in the management of this condition.…”
Section: Introductionmentioning
confidence: 99%